A New Lebanese Medication Adherence Scale: Validation in Lebanese Hypertensive Adults. (20th May 2018) - Bou Serhal, R.; Salameh, P.; Wakim, N.; Issa, C.; Kassem, B.; Abou Jaoude, L.; Saleh, N.
Abstract : Background. A new Lebanese scale measuring medication adherence considered socioeconomic and cultural factors not taken into account by the eight-item Morisky Medication Adherence Scale (MMAS-8). Objectives were to validate the new adherence scale and its prediction of hypertension control, compared to MMAS-8, and to assess adherence rates and factors. Methodology . A cross-sectional study, including 405 patients, was performed in outpatient cardiology clinics of three hospitals in Beirut. Blood pressure was measured, a questionnaire filled, and sodium intake estimated by a urine test. Logistic regression defined predictors of hypertension control and adherence. Results. 54.9% had controlled hypertension. 82.4% were adherent by the new scale, which showed good internal consistency, adequate questions (KMO coefficient = 0.743), and four factors. It predicted hypertension control (OR = 1.217; p value = 0.003), unlike MMAS-8, but the scores were correlated (ICC average measure = 0.651; p value < 0.001). Stress and smoking predicted nonadherence. Conclusion . This study elaborated a validated, practical, and useful tool measuring adherence to medications in Lebanese hypertensive patients.